β-blocker in Heart failure with reduced ejection fraction: A review - Adhikari, Chandra Mani (Nepalese Heart Journal, 2014)
Heart failure, a major public health problem is associated with high mortality, poor quality of life, and frequent hospitalization. It is a complex syndrome characterized by neurohumoral activation. Activation of sympathetic nervous system plays an important role in its pathogenesis. Randomized trials have show that β-blockers reduce mortality, hospitalization and improves quality of life. One of the three β-blockers (i.e., bisoprolol, carvedilol, and sustained-release metoprolol succinate) is recommended for all patients with current or prior symptoms of Heart Failure, unless contraindicated, to reduce morbidity and mortality. β-blockers are underused in patients with heart failure. If a patient is considered suitable for β-blocker therapy, a careful initiation and gradual increases of β-blocker dose are crucial to avoid clinical deterioration. Initiating the Angiotensin Conventing Enzyme inhibitor first is traditional but studies have proven similar safety with a β-blocker-first strategy. Emerging evidence suggests that the order of initial ACEI or β-blocker therapy may not matter. Nepalese Heart Journal | Volume 10 | No.1 | November 2013| Pages 38-45 DOI: http://dx.doi.org/10.3126/njh.v10i1.9746